The Jamestown Lectures 2006-2007 : the Rule of Law. - COMBAR (Hart Pub., 2008)
In April 2007 COMBAR held its annual meeting in conjunction with the University of Richmond, Virginia. The timing of the meeting was designed to form part of the celebrations of the 400th anniversary of the signing of the Virginia Charter and the founding of Jamestown. The conference which was conducted at the meeting took as its topic The Rule of Law, and brought together lawyers from around the common law world (and some from outside) to debate the meaning and importance of this fundamentally important topic. Judges from the UK Court of Appeal and House of Lords were present to take part, al.